INTERNET OF THINGS (IOT) AND NEW BUSINESS OPPORTUNITIES IN THE CREATIVE SECTOR - Loso Judijanto; Haruka Sato; Miku Fujita; Ardi Azhar Nampira (Journal of Social Entrepreneurship and Creative Technology, 2025)
The rapid growth of the Internet of Things (IoT) has led to significant advancements in various industries, including the creative sector. IoT technology enables the interconnection of devices and systems, allowing for new forms of interaction and automation. However, the potential of IoT to generate new business opportunities within the creative industries has not been fully explored. This research aims to investigate the impact of IoT on the creative sector, focusing on how businesses can leverage IoT to innovate, enhance customer experiences, and streamline operations. The study adopts a qualitative research approach, combining case studies and interviews with industry professionals to explore the current applications of IoT in design, media, entertainment, and the arts. The findings indicate that IoT technologies have the potential to revolutionize the creative sector by enabling personalized experiences, optimizing creative workflows, and creating new revenue streams. Businesses are increasingly adopting IoT to offer interactive experiences, such as smart installations, personalized content, and enhanced product design. The study concludes that IoT can offer substantial business opportunities for companies in the creative sector, especially when it comes to enhancing customer engagement and integrating technology into traditional creative processes.